Suppressing charge recombination in a methylammonium-free wide-bandgap perovskite film for high-performance and stable perovskite solar cells - Ye, Qiufeng; Hu, Wenzheng; Zhu, Junchi; Cai, Ziyu; Zhang, Hengkang; Dong, Tao; Yu, Boyang; Chen, Feiyang; Wei, Xieli; Yao, Bo; Dou, Weidong; Fang, Zebo; et al. (Energy & environmental science, 2024)
Wide-bandgap (WBG) formamidinium-cesium (FA-Cs) hybrid lead iodide-bromide mixed perovskites (∼1.7 eV) have gained great attention with the potential of enabling highly efficient tandem photovoltaics when integrated with crystalline silicon and other low-bandgap solar cells. However, their power conversion efficiencies (PCEs) are still insufficient compared to their methylammonium (MA) counterparts, mainly owing to the high open-circuit voltage ( V OC ) deficits (>0.43 V). Here, by incorporating rubidium iodide (RbI) in the FA 0.8 Cs 0.2 Pb(I 0.75 Br 0.25 ) 3 perovskite precursor, the film crystallinity and bulk defects are significantly optimized. In addition, we propose an all-around interface engineering strategy sequentially constructing a surface heterojunction and using trioctylphosphine oxide (TOPO), which can significantly passivate grain boundaries and undercoordinated defects, as well as optimize the energy band. As a result, the target MA-free WBG n-i-p solar cells at 1.685 eV have achieved a record efficiency of 23.35% and a high V OC of 1.30 V (with a record voltage deficit of 0.385 V). Most importantly, the unencapsulated solar cells also display impressive air storage stability, operating stability and thermal stability. Moreover, a PCE of 19.54% on a 1 cm 2 WBG solar cell and a PCE of 21.31% on a 0.04 cm 2 p-i-n inverted WBG solar cell are also demonstrated. We employed RbI additive, constructed heterojunction, and used TOPO post-treatment for suppressing non-radiative recombination of MA-free WBG perovskite. The device showed a record PCE of 23.35%, a high V OC of 1.3 V and the impressive stability.